(untitled) (Journal of the College of Basic Education, 2022)
Classroom interaction is on of education topies that require special attention for those interested in the field of education ,where are longer the methods of teaching of classroom and that ,overlook this side are useless and not fit to students of the day, The research has tow aims , the first : is disclosure of prevailing patterns classroom interaction for teachers of chemistry in junior high school and the extend of its focus on the activity of each student and the teacher in chemistry lessons .The second : identify the effect of the three patterns of teaching ,and classified according to the ratio of the concentration of classroom interaction in thinking variables high-grade and achievement in chemistry through the nine hypotheses zero . the goal of research is completed by two phase Bgesatin ,the first –is descriptive to disclosure of three paterns classroom interaction (concentration on teacher, participatory, concentration on student ) which the teachers of chemistry are using in fifth grads science in chemistry lessons and give its attributed ,while the second-is experimental grade to give the patterns teaching in the variable of research .and found that: 1-The pattern participatory is the most influential in thinking high-grade in chemistry for the students ingeneral ,and there is no influential on achievement. 2- The female students are better more than male in their thinking and achievement of chemistry. - This research has several recommendations one of them in the necessity to workout concentration pattern about the student in chemistry lessons in our schools according to its modern effectiveness and trends in teaching. - The researcher provides future proposals an update to the current research included seta study about the effect of the three patterns of teaching in cognitive , skill, and sentimental variables of the students in different school levels .